Advanced applications of chemo‐responsive dyes based odor imaging technology for fast sensing food quality and safety: A review. Issue 5 (18th August 2021) - Kang, Wencui; Lin, Hao; Jiang, Hao; Yao‐Say Solomon Adade, Selorm; Xue, Zhaoli; Chen, Quansheng
Abstract: Public attention to foodquality and safety has been increased significantly. Therefore, appropriate analytical tools are needed to analyze and sense the food quality and safety. Volatile organic compounds (VOCs) are important indicators for the quality and safety of food products. Odor imaging technology based on chemo‐responsive dyes is one of the most promising methods for analysis of food products. This article reviews the sensing and imaging fundamentals of odor imaging technology based on chemo‐responsive dyes. The aim is to give detailed outlines about the theory and principles of using odor imaging technology for VOCs detection, and to focus primarily on its applications in the field of quality and safety evaluation of food products, as well as its future applicability in modern food industries and research. The literatures presented in this review clearly demonstrated that imaging technology based on chemo‐responsive dyes has the exciting effect to inspect such as quality assessment of cereal, wine and vinegar flavored foods, poultry meat, aquatic products, fruits and vegetables, and tea. It has the potential for the rapid, reliable, and inline assessment of food safety and quality by providing odor‐image‐basedmonitoring tool. Practical Application : The literatures presented in this review clearly demonstrated that imaging technology based on chemo‐responsive dyes has the exciting effect to inspect such as quality assessment of cereal, wine and vinegar flavored foods, poultry meat, aquatic products, fruits and vegetables, and tea.